2012
DOI: 10.1590/s1984-29612012000200012
|View full text |Cite
|
Sign up to set email alerts
|

Detection and molecular characterization of piroplasms species from naturally infected dogs in southeast Brazil

Abstract: Rangelia vitalii is a protozoon described from dogs in the south and southeast regions of Brazil. It is phylogenetically related to Babesia spp. that infects dogs, but data on this enigmatic parasite is still limited. The aim of this work was to detect piroplasm species in dogs in the state of Rio de Janeiro, Brazil, by 18S rRNA gene-based PCR assay, restriction fragment length polymorphism (RFLP) and sequence analyses. Of 103 dogs examined, seven (6.8%) were positive for Babesia spp. by PCR. The amplified pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 21 publications
2
30
0
4
Order By: Relevance
“…Rangelia vitalii and Babesia vogeli are morphologically indistinguishable, and species differentiation is done by PCR and genetic sequencing (LEMOS et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Rangelia vitalii and Babesia vogeli are morphologically indistinguishable, and species differentiation is done by PCR and genetic sequencing (LEMOS et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Forward primer Bab 143-167 (5´-CCG TGC TAA TTG TAG GGC TAA TAC A-3´) and reverse primer Bab 858-834 (5´-CCT CTG ACA GTT AAA TAC GAA TGC C-3´) were used in the PCR reaction, which amplified fragments of approximately 700 bp from the gene that encodes the 18S region of piroplasm RNA (SOARES et al, 2011;LEMOS et al, 2012).…”
Section: Dna Extraction Amplification and Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a need for a different method of diagnosis because of the similarity of this disease with canine babesiosis (MORITA et al, 1995;LEMOS et al, 2012). Hence, the objective of this research was to characterize cases of canine rangeliosis identified in the Setor de Patologia Veterinária at Universidade Federal do Rio Grande do Sul (SPV-UFRGS) based on epidemiology, hematology and gross and histopathology in addition to the molecular detection and sequencing of genetic material.…”
Section: Introductionmentioning
confidence: 99%